Demographics and perceptions of diversity in dermatopathology workforce and training environments in the United States. (22nd November 2022) - Ahmed, Aadil; Gittens, Brian E.; Stewart, Scott A.; Shalin, Sara C.
Abstract: Objectives: The aim of this study was to determine the demographics and perceptions of diversity, equity, and inclusion (DEI) in the field of dermatopathology to provide a measurable baseline for future efforts to enhance equity measures within our subspecialty. Methods: A questionnaire based on a previously validated instrument by Association of American Medical Colleges (AAMC) was sent to American Society of Dermatopathology (ASDP) members to collect the demographic information (gender, race, sexual orientation, disability, experience and practice setting, etc.) and evaluate eight diversity, engagement, and inclusivity statements on a 1–5 Likert scale. Results: The demographics of 207 of 1331 (15%) respondents showed slight male predominance. Eleven percent of respondents identified as LGBTQI. The major racial distribution was comprised of 62% White, 18% Asian (including Middle Eastern/Indian), 10% Hispanic, and 4% Black respondents. New‐in‐practice respondents (those in practice—5 years or less) were more likely to have a pathology background (71% vs. 56%, p  = 0.047) than their more‐established peers with more than 5 years of service. This trend also contributed to increased diversity in terms of gender (66% females) and race (48% non‐White) among the newer generation. Dermatology‐trained dermatopathologists were mostly White (70%) and male (53%). Analysis of respondent demographics with perception statements showed that White and US graduate respondents (compared to other groups) were more likely to have a positive perception about DEI within the field of dermatopathology. Conclusions: The results provide a snapshot of the current state of diversity within the field of dermatopathology. Moreover, these results highlight opportunities for further increasing diversity in general and leadership in particular within dermatopathology.